2011
DOI: 10.1371/journal.pone.0022672
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Knockdown of Ribosomal Protein Gene RPL19 Abrogates the Aggressive Phenotype of Human Prostate Cancer

Abstract: We provide novel functional data that posttranscriptional silencing of gene RPL19 using RNAi not only abrogates the malignant phenotype of PC-3M prostate cancer cells but is selective with respect to transcription and translation of other genes. Reducing RPL19 transcription modulates a subset of genes, evidenced by gene expression array analysis and Western blotting, but does not compromise cell proliferation or apoptosis in-vitro. However, growth of xenografted tumors containing the knocked-down RPL19 in-vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 108 publications
1
45
0
Order By: Relevance
“…rpS2 was reported to be a therapeutic targeting for the eradication of prostate cancer in preclinical tumor modeling studies31. Silencing of rpL19 abrogated the aggressive phenotype of human prostate cancer32.…”
Section: Discussionmentioning
confidence: 99%
“…rpS2 was reported to be a therapeutic targeting for the eradication of prostate cancer in preclinical tumor modeling studies31. Silencing of rpL19 abrogated the aggressive phenotype of human prostate cancer32.…”
Section: Discussionmentioning
confidence: 99%
“…These RPLP protein-deficient cells have high levels of intracellular ROS, and it is recognized that deregulation of the cellular redox state can impact the levels and activity of TP53. 51,52 Higher levels of ROS appear to be part of a feed-forward loop that stabilizes TP53, which may occur in MCF-7 cells treated with 3-MA, resulting in increased TP53 activity that interferes with mitochondrial function and/or integrity, and eventually contributes to cell death. 53 Recent research reveals that autophagy is activated by TP53 and members of the MAPK11/12/13/14 family.…”
Section: Discussionmentioning
confidence: 99%
“…And the secretion was positively correlative with degree of drug-resistance and malignance of cancer cells (Kim et al, 2013). RPL19 was highly expressed in some prostate cancers and colorectal cancers, and it was studied as a prognostic biomarker for these two cancers (Bee et al, 2011;Yang et al, 2010;Huang et al, 2008;Bee et al, 2006). In addition, RPS15A (Xu et al, 2013), RPL26 and RPL29 (Li et al, 2012) were also found to be associated with cancer cells proliferation.…”
Section: Introductionmentioning
confidence: 97%